The Influence of Thickness on Low Carbon Steel in Rapid Cooling Process - Norazlianie, Sazali; Wan Norharyati, Wan Salleh; Ihsan Naiman, Ibrahim; Haziqatulhanis, Ibrahim; Mohd Syafiq, Sharip (Akademi Baru, 2019)
Hot stamping is among the latest technology applied in sheet metal manufacturing. It is a combination of a forming and rapid cooling to produce stronger products with the creation of martensite inside the sheet metal components. To cope with a huge range of sheet metal that suitably used for hot forming process, this research investigates microstructure changes during the rapid cooling process of three different sheet metal thicknesses. The Low Carbon Steel specimens of 2, 4 and 6mm thick were heated in a furnace shows that 2mm specimen is the fastest cooling for both cooling processes compared to 4mm and 6mm specimens. The 2mm specimen of water quench formed a higher percentage of martensite and compactly bonded structure compared to 4mm and 6 mm specimens' structure.